The frictional contact problem of a rigid punch sliding over thermoelectric materials. (September 2020) - Tian, X.J.; Zhou, Y.T.; Guan, X.F.; Wang, L.H.; Ding, S.H.
Abstract: A theoretical frictional contact model of thermoelectric materials with nonlinear thermoelectric coupling loaded by a sliding punch is considered in which the punch is also assumed to be an electrical and thermal conductor. For the electric fields and the temperature fields, some analytical results are obtained by Fourier transform technique, such as the full field closed-form formulas of the electrochemical potential, the temperature, the electric current density and the energy flux. The distributions of normal electric current density and normal energy flux at subsurface are graphically given. For the elastic fields, the thermoelastic contact problem is reduced to a singular integral equation of the second kind in which thermoelectric effects are reflected in the right end of the resulting equation. The present results demonstrate that the normal electric current density, the normal energy flux and the contact pressure on the contact surface of thermoelectric materials exhibit high singularity in the vicinity of the edges of the punch. Furthermore, the effects of the friction coefficient and the thermoelectric loads on the critical stresses, the electric current density intensity factor, the energy flux intensity factor and the stress intensity factor are provided. The finding of the presented model is helpful for accessing the surface wear resistance of thermoelectric materials.